Computer-Aided Grinding Process of Oil Seeds - Grzegorz SMIGIELSKI; Krzysztof TYSZCZUK (Communications of International Proceedings, 2020)
The grinding process of oil seeds requires careful selection of grinder input parameters to obtain a product with appropriate physical and chemical properties. The article presents a precise grinder design (with a measurement and control unit, and a genetic algorithm module), which facilitates selection of optimal settings of the mill during the industrial grinding process.
Keywords: Grinding; Dietary Supplements; Genetic Algorithm; Manufacturing System Technologies.